An exploratory case study of the effects of gender related combat stress on adult learning in a military academic environment - Berg, Paul Eric (Kansas State University, 2016)
This study describes how combat experiences affected female Army officers who attended the Command and General Staff College (CGSC) in Fort Leavenworth, Kansas. The female Army officers’ combat experiences were found to affect their academic learning, classroom experience, and coping mechanisms in a graduate-level professional military education. The themes identified included combat-related gender specific experiences and additional gender themes related to learning in a male-dominated military education environment. Nine female active duty Army officers who were attending CGSC participated in this research with each having a minimum of two combat tours. In addition, two active duty Army CGSC military instructors with multiple combat tours and two behavioral counselors specializing in military patients were also interviewed. The findings of this case study indicated that combat experiences affect t a degree the female students who served in the Army in Iraq and Afghanistan. The level of perceived academic stress was contingent upon the impact of the CGSC classroom environment, personal combat experiences, prior education, gender related combat stress, and other factors. Also, the learning experience of female students at CGSC was influenced due to marginalization in the classroom, instructor biases, and two-female limitations. This study contributes the continued research on effects of combat on adult learning, specifically adding to the limited works on being a female serving in the Army.
Keywords: Adult education; Command and General Staff College; Combat stress; Women in military